At first sight ebook - Sparks, Nicholas (Jeremy Marsh, 2005)
In this #1 New York Times bestselling follow-up to True Believer , a young couple's love faces the ultimate test when the past disrupts the life and family they've built together. There are a few things Jeremy Marsh was sure he'd never do: he'd never leave New York City; never give his heart away again after barely surviving one failed marriage; and, most of all, never become a parent. Now, Jeremy is living in the tiny town of Boone Creek, North Carolina, married to Lexie Darnell, the love of his life, and anticipating the birth of their daughter. But just as his life seems to be settling into a blissful pattern, an unsettling and mysterious message re-opens old wounds and sets off a chain of events that will forever change the course of this young couple's marriage. Dramatic, heartbreaking and surprising, this is a story about the love between a man and a woman and between a parent and a child. More than that, it is a story that beautifully portrays how the same emotion that can break your heart is also the one that will ultimately heal it. While the novel picks up the tale of Lexie Darnell and Jeremy Marsh that started in True Believer and will delight fans of that novel, it stands on its own as one of Nicholas Sparks's most deeply moving love stories.